Propuesta para Fomentar el Liderazgo y el Desarrollo Comunitario del Barrio Central de la Parroquia Rural Jimbilla del Cantón Loja, y la Intervención del Trabajador Social - Sedamanos Washco, Gissella Anabel (2018)
The present research work entitled; "Proposal to promote leadership for community development in the central neighborhood at Jimbilla rural parish of the Loja, and the intervention of the Social Worker", it contemplates a community study, whose general objective was to improve the community leadership of people who live in the central neighborhood of the rural Parish Jimbilla of the Loja. This research is based theoretically and methodologically through the categories of the object in study that allows to identify the research, diagnose of the leadership state, and design of a proposal to promote the leadership for community development. The applied methodology was the Community Self-Development of the author Dr. Ramón Rivero was used in three stages that were applied: first stage initial exchange with the subject in need of professional action, second stage was the exploration of the stage and the third stage was the Diagnosis and search of solutions, using techniques and instruments such as: observation, brainstorming, interviews directed to the parish leaders and surveys applied to residents of the central neighborhood and finally the return of the information and it was made through a meeting with people of community. Among the main findings got in the present research, let us the absence of leadership in the central neighborhood at Jimbilla parish, itself reveals the participatory lack of interest between people where the main causes that have to do with division, poor communication, authoritarianism and the division of the community by political rivalries that affect the development and progress of the neighborhood. People in order consider that the way to improve leadership, unity and teamwork are necessary where both; young people and adults can be involved, giving a meaningful contribution that can prevail within the community with the purpose to achieve community development. Faced to hese results, together with the community, strategies were proposed to strengthen the leadership for community development that will help the community. The conclusions and recommendations are aimed to achieve the objectives of the present research.